Creating Shared Value (CSV) based on the system in yoga related to corporate awareness in the practice of Corporate Social Responsibility (CSR) - Devica Pratiwi (Universitas Hayam Wuruk Perbanas, 2021)
Along with the changing time, CSR activities carried out by companies currently have been able not only to improve the welfare of the community but also to create shared value. In this concept, companies must be aware that creating shared value (CSV) is able to produce benefits to be shared and is more than just focusing on social responsibility. Companies should not only take corrective actions, but also reorganize the business strategies they use starting from the stages of planning and production to the stage of distribution to the end consumer, while still considering the factors of the company (economy), human and environment, or often referred to as the triple bottom line (profit, people, planet). This study aims to observe the development and disclosure of CSV in companies by using sustainability reports based on the system in yoga. Judging from the type of data, the approach used in this study is a qualitative descriptive approach. The research data used is the Sustainability Reports of Coca-Cola Company, Ltd., Nestle, and PT. Unilever Indonesia, Tbk for 2018. The results of this study show that the three companies have implemented CSV activities which are expressed in 5 Yamas Yoga: Ahimsa/non-violence; Satya / truthfulness / non-falsehoods; Asteya / honesty, non-stealing; Brahmacharya / Self-control; and Aparigraha / non-possessiveness, non-greediness. not expecting, asking, or accepting inappropriate gifts from any person.